On the existence of a generalized asymmetric (α, β)-spline whose average values have equal minima at given points - Skorokhodov, D. S. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We solve the problem of existence of an asymmetric spline averaged in Steklov’s sense that takes equal minimum values at given points.